Law Enforcement of Money Laundering: Case Studies on Fighting Narcotic Crime - Alamsari, Sri Heny (2019)
The research was based on the fact of increasing narcotics crime, both quantitatively and qualitatively as well as it has begun become a transnational organized-crime. It is an empirical-legal research. The site of research was the National Narcotics Agency. It was designed to look at the relationship between the three independent variables (investigation, arrest, and investigation of drug leader assets) on the effectiveness of law enforcement on the drug leader case as dependent variable. The hypothesis of research indicates that the more intense of investigation, arrest and investigation of narcotics asset, the higher of effectiveness of law enforcement in narcotics leader case. Keywords: Narcotics, Money Laundering, Transnational Crime DOI: 10.7176/JLPG/88-22 Publication date: August 31st 201